Prestimulus beta power and phase synchrony influence the sound-induced flash illusion - Keil, Julian; Müller, Nadia; Hartmann, Thomas; Weisz, Nathan (Cerebral Cortex, 2014)
We investigated the sound-induced flash illusion, an example for the influence of auditory information on visual perception. It consists of the perception of 2 visual stimuli upon the presentation of a single visual stimulus alongside 2 auditory stimuli. We used magnetoencephalography to assess the influence of prestimulus oscillatory activity on varying the perception of invariant stimuli. We compared cortical activity from trials in which subjects perceived an illusion with trials in which subjects did not perceive the illusion, keeping the stimulation fixed. Subjects perceived the illusion in approximately 50% of trials. Prior to the illusion, we found stronger beta-band power in left temporal sensors, localized to the left middle temporal gyrus. Illusory perceptions were preceded by increased beta-band phase synchrony between the left middle temporal gyrus and auditory areas as well as by decreased phase synchrony with visual areas. Alpha-band phase synchrony between visual and temporal, parietal, and frontal cortical areas as well as alpha-band phase synchrony between auditory and visual areas were modulated. This supports and extends reports on the influence of brain states prior to stimulation on subsequent perception. We suggest that prestimulus local and network activities form predispositions if sensory streams will be integrated. © 2013 The Author.
Created from Fastlane, Scopus look-up
Keywords: audiovisual illusion; connectivity; magnetoencephalography; oscillatory activity; perception